(untitled) (Eurasian Journal of Ecology, 2016)
The characterisation of the hydrochemical and toxicological situation of Ural in 2011-2013 seasonal year. The changes in total mineralization, permanganate oxidation, the content of nitrates, nitrites and heavy metals is showed. A quantitative evaluation of pollutants at Ural river water is given. Transborder pollution, coming to the area on the Ural River with Flood and low flow is calculated. The changes of the chemical composition of the river. Installed pollution on individual components (copper, zinc, chromium (VI) iron) is given.